1996
DOI: 10.1016/s0969-2126(96)00016-0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of various maltooligosaccharides bound to maltoporin reveal a specific sugar translocation pathway

Abstract: Hydrophobic interactions with the greasy slide guide the sugar into and through the channel constriction. The glucosyl-binding subsites at the channel constriction confer stereospecificity to the channel along with the ability to scavenge substrate at low concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
190
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(203 citation statements)
references
References 31 publications
12
190
0
1
Order By: Relevance
“…The saccharide-aromatics interactions have to be clarified for the analysis of the permeation process, because it makes a difference whether the observed ribbon of aromatic side chains were a continuous "greasy slide" (Dutzler et al, 1996), or a row of separated attracting patches. In the absence of sufficient physicochemical data, we performed a statistical analysis of the observed saccharide binding sites and converted it to interaction energies.…”
Section: G3-g2-g1mentioning
confidence: 99%
“…The saccharide-aromatics interactions have to be clarified for the analysis of the permeation process, because it makes a difference whether the observed ribbon of aromatic side chains were a continuous "greasy slide" (Dutzler et al, 1996), or a row of separated attracting patches. In the absence of sufficient physicochemical data, we performed a statistical analysis of the observed saccharide binding sites and converted it to interaction energies.…”
Section: G3-g2-g1mentioning
confidence: 99%
“…An even number of transmembrane b strands ranging from 8 to 22 has been observed in b-barrel membrane proteins of known crystal structure. Examples are the bacterial outer membrane proteins (OMPs), such as outer membrane protein A (OmpA) with 8 b strands (b-s) [5,6], OmpT (10 b-s) [7], OmPlA (12 b-s) [8], OmpF (16 b-s), maltose (LamB) [9,10] or sucrose (ScrY) [11] porins (18 b-s), and the iron transporters FhuA [12,13] or FepA [14] (22 b-s) (see fig. 1 for some examples).…”
Section: Introductionmentioning
confidence: 99%
“…These ionizable residues are arranged pairwise but in most cases are too far apart from each other to form salt bridges, thus they constitute potential hydrogen bond donors/acceptors with substrates (7). Crystallographic studies (8) have shown that sugars are involved in van der Waals' contacts with the greasy slide via the hydrophobic face of their glycosyl ring. Multiple H bonds are formed between the sugar hydroxyl groups and the charged residues of the two ionic tracks.…”
mentioning
confidence: 99%
“…Multiple H bonds are formed between the sugar hydroxyl groups and the charged residues of the two ionic tracks. Constant breaking and remaking of these hydrogen bonds has been suggested to allow movement of the substrate through the channel (8,9). The role of the greasy slide in sugar translocation through the channel will be discussed in a future paper.…”
mentioning
confidence: 99%